Ikonen der Nation : Heldendarstellungen im post-sozialistischen Kroatien und Serbien - Sabo, Klaudija (Verlag der Österreichischen Akademie der Wissenschaften, 2017)
The book icons of nations is dealing with the transformation processes in ex-Yugoslavia in the early 90s that is focussing on the national myths and their heroes and heroins in the region and their representation in visual culture